Updated Long‐Term Trends in Mesopause Temperature, Airglow Emissions, and Noctilucent Clouds. Issue 5 (4th March 2020) - Dalin, P.; Perminov, V.; Pertsev, N.; Romejko, V.
Abstract: We have updated long‐term trends in mesopause temperature, airglow emission intensities, and noctilucent clouds (NLCs) based on ground‐based observations conducted in the Moscow region (Russia). Trends in mesopause temperature and airglow emissions have been derived for the period 2000–2018 (19 years), and long‐term trends in NLC characteristics have been obtained for 1968–2018 (51 years). Trends in airglow emissions have been estimated separately for winter and summer seasons. There are statistically significant negative trends in molecular oxygen O2 A(0‐1) and hydroxyl OH(6‐2) emission intensities in both winter and summer. Responses of the airglow intensities to solar activity have been found to be significantly positive, with winter ones being 1.5–2 times greater than summer ones. There is a rather strong and statistically significant cooling of the summer mesopause at a rate of −2.4±2.3 K/decade, whereas the winter mesopause demonstrates a small and statistically insignificant cooling of −0.4±2.2 K/decade. The response of the mesopause temperature to solar activity is positive and about 2 times greater in winter than in summer. We consider long‐term trends in the summer mesopause temperature and NLC for the same time period and same geographical region. Secular trends in NLC parameters have been found to be small and statistically insignificant as observed from midlatitudes. NLCs demonstrate statistically significant negative response to solar activity. Ozone forcing produces minor effects on both airglow and NLC characteristics. The observed small secular NLC trends contradict large modeled NLC trends recently obtained by Lübken et al. (2018, https://doi.org/10.1029/2018GL077719 ). Key Points: There are statistically significant negative trends in molecular oxygen and hydroxyl OH(6‐2) emission intensities in both winter and summer Secular trends in NLC parameters have been found to be small and statistically insignificant as observed from midlatitudes Responses of airglow intensities to solar activity are significantly positive, with winter ones being 1.5–2 times greater than summer ones